Exploring endoperoxides as a new entry for the synthesis of branched azasugars - Svenja Domeyer; Mark Bjerregaard; Henrik Johansson; Daniel Sejer Pedersen (Beilstein Journal of Organic Chemistry, 2017)
A new class of nitrogen-containing endoperoxides were synthesised by a photochemical [4 + 2]-cycloaddition between a diene and singlet oxygen. The endoperoxides were dihydroxylated and protected to provide a series of endoperoxide building blocks for organic synthesis, with potential use as precursors for the synthesis of branched azasugars. Preliminary exploration of the chemistry of these building blocks provided access to a variety of derivatives including tetrahydrofurans, epoxides and protected amino-tetraols.